The Evolution Of Corporate Governance In China : The Role Of Institutional Investors - Jing, Wang (2005)
The objective of this paper ar eto provide a brief historical description of the process of corporate governance reform in China, and provide a comprehensive assessment of the existing state of institutional investors; reviews institutional capacity and the regulatory environment, and discuss the existing structure and activities of institutional investors in China, the monitoring role of institutional investors.